Program design considerations for bone health in premenopausal women - Tracey Clissold; John B Cronin; Mary Jane De Souza; Paul W Winwood (Archives of Sports Medicine and Physiotherapy - Peertechz Publications, 2022)
The purpose of this literature review is to critique training studies that have examined the effects of jump-landing programmes on bone health parameters in premenopausal women.  Activities such as jumping and hopping have been proposed to achieve the desired unusual or atypical strain distributions on the skeleton for women who are habitually inactive and not involved in high-impact sports, however specific protocols to optimise bone health are currently lacking. From this review, it can be concluded that jump-landing protocols that; utilise brief jumping episodes (10 - 100 jumps/day, 3 - 7 days/week), are 4 - 18 months duration, and present loading magnitudes of between 2 - 6 body weights (BW) and rates of >43 BW.sˉ¹, can result in significant gains in femoral neck bone mineral density of 0.6 - 3.4% in premenopausal women. Evidence from this review has the potential to inform future exercise recommendations used to improve bone health during the critical premenopausal period, and to both reduce and delay the incidence of osteoporotic fracture in the years post menopause.